The Quality of the Department of Library Science's Website by WebQual 4.0 - Andi Ibrahim; Touku Umar; Feri Ardinata (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
This research discusses the quality of the website of the Library Science Study Program Universitas Islam Negeri Alauddin Makassar as a medium of information using the WebQual 4.0 method. Three measurement variables are used, namely: Usability Quality, Information Quality, and Interaction Quality. This descriptive study uses a quantitative approach in presenting data. The data were obtained through online questionnaires and website observations. The population in this study was 448,440 the number of website visitors and a sample of 100 student respondents who were determined by incidental sampling technique. The validity and reliability tests used SPSS 23 software. The results showed that the quality of usability and information quality of the website of the Department of Library Science UIN Alauddin Makassar were in the good category with a percentage of 75.1% and 73.7%. Meanwhile, the interaction quality is in the very good category with a percentage of 81.5%. So it can be said that the quality of this website is in a good category.